Spatial Mapping and Potential Analysis of Solar Farm Prospective through GIS Utilization as Energy Sovereignty Technical Consideration for the New National Capital City (IKN) Area Development - Andoko, Stella Eulia; Wibowo, Adnan Hasyim; Hanabila, Annesa (NBRI Press, 2023)
Solar energy makes up around 50% of Indonesia's renewable energy potential. Yet, only 0.08% has been utilized in 2021. In order to achieve the 2050 Sustainable Development Goals, a solution to help the acceleration towards renewable energy needs to be done, especially in New National Capital City (IKN) area development. Hence, the researchers came up with the idea of spatial mapping and potential analysis for renewable energy technologies, specifically solar farms in the IKN development area through Geographical Information System (GIS) utilization. The researchers map the suitable areas for solar energy tapping based on solar radiation data which provides a picture of the potential and assesses the feasibility for its development by integrating various datasets and spatial analysis. This paper is a mixed method research that applies the 4D (define, design, deliver, and discover) method to collect data and perform spatial mapping and potential analysis on data processing. The results of this study indicates that the IKN development area has significant potential for solar energy generation due to their favorable solar irradiance levels, land availability, and proximity to existing infrastructure. The findings of this study aims to contribute to the goal of achieving energy sovereignty in the IKN area development by providing valuable insights for decision-makers involved in energy planning and development through GIS analysis. However, this paper still has various shortcomings. Therefore, it is recommended for future research to undertake a comprehensive economic feasibility study to evaluate the viability of solar projects in the IKN development area.